EKSISTENSI HUKUM HINDU DALAM HUKUM ADAT DI TENGAH PERUBAHAN SOSIAL DI DESA ADAT BANJAR TANGGAHAN PEKEN DESA SULAHAN KECAMATAN SUSUT KABUPATEN BANGLI - i gede januariawan (VYAVAHARA DUTA, 2023)
Hindu Law and Customary Law in Bali are very closely related, so that it often creates confusion about which understanding is Hindu Law and which is Customary Law. During the Raad Kerta period, Van den Berg's theory of receptio in complexu stated, "If a community embraces a certain religion, then the customary law of the community concerned is the religious law it embraces". Based on this theory, the customary law that applies in Bali is Hindu law. In fact, the law continues to change according to the needs of society and the times. Along with the current epidemic that hit the world, it caused changes in all aspects of life, including in the field of law. The flow of globalization also brings changes to the values in people's lives which creates various kinds of problems so that it needs to be regulated by the rule of law as law making and law enforcement or law enforcement. In the field of Customary Law, the possibility of change is also very large, especially with the issuance of Regional Regulation No. 4 of 2019 concerning Traditional Villages in Bali. This regional regulation in such a way strengthens the position of the MDA (Traditional Village Council) which encourages the establishment of new regulations in the Traditional Village. Changes are likely to have occurred in customary law in the areas of Law of Pearahan, Pawongan, and Palahan. This research will try to reveal the existence of Hindu law which is still a living law in indigenous peoples. The problems in this study are discussed with the theory of Sociological Jurisprudence and Theory of Social Change. As for the results of his research that in the area of influence, Hindu law is very clear because it regulates the relationship between humans and God, which is called Ida Sang Hyang Widhi, with all its manifestations, called Tri Murti. Also known as the worship of the local Gods called Batara and Batari with all forms of accompanying religious ceremonies. In the field of pawongan, the influence of Hindu law is still strong regarding the existence of village krama who have an obligation to organize all forms of religious ceremonies. Likewise in the field of family law, marriage and inheritance. In the field of pekaahan, regarding the relationship between humans and the environment, it is still in accordance with Hindu law that the environment is regulated in awig-awig and perarem.